PERBANDINGAN EFEKTIVITAS PENDEKATAN PEMBELAJARAN SAVI DAN KONTEKSTUAL DITINJAU DARI PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP MUHAMMADIYAH MERAUKE - Wahyu Siti Irianti; Etriana Meirista; Murni Sianturi (Musamus University, 2018)
This study aims to find out the first, the effectiveness of SAVI learning approach in mathematics learning of students of Muhamadiyah Merauke. The second, the effectiveness of contextual approach used in mathematics learning viewed from mathematics learning achievement of students of SMP Muhammadiyah Merauke. And the third, the comparison of effectiveness between SAVI learning approach and contextual method viewed from of learning achievement in mathematics. This research is an experimental research and the design used pretest-posttest control group design. The population of this research is grade VIII B students of SMP Muhammadiyah Merauke selected by cluster random sampling technique. The technique of data collection was test and the instrument was learning achievement test. The testing of first and second hypothesis used paired sample of z-test while the third hypothesis testing was done using independent sample of z-test. Based on the analysis of the first hypothesis data, it was obtained, which means thatis rejected and is accepted. This means that the SAVI learning approach is effectively used in learning in terms of students' mathematics learning achievements. Analysis of the second hypothesis data, it was obtained, which means that is rejected and is accepted. This means that the contextual learning approach is effectively used in learning in terms of students' mathematics learning achievements. Then the third hypothesis data, the comparison of mean of posttest data was obtained, which means thatis rejected andis accepted. This means that the SAVI learning approach is more effective than contextual learning approaches in terms of students' mathematics learning achievement.